Analisa Meningkatnya Kasus Food Piracy dalam Fenomena Italian Sounding - Audi Muhammad; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Italian food product is a very popular product in the world and this fact leads to a largenumber of counterfeiting cases to these products. This can be seen from the large amountof profit reaching 30 billion Euro and ascend to 60 billion Euro. This research aim todetermine the cause of the increasing case of food piracy in the Italian Soundingphenomena in spite of the Italy’s numerous effort in handling this case. This research usesTransnational Organized Crime theory which will then be continued by usingneoliberalism view in the form of International Cooperation theory, InternationalInstitution theory, and International Regime theory. The method used for this research isqualitative with explanative research type. This research proves that the cause of this casecontinues to increase is the lack of awareness from Italy and other countries regarding thiscase which leads to the lack of international cooperation initiative in respond to foodpiracy in the Italian Sounding phenomena case.